Transforming Junior High Student Elections: The Impact of Pancasila Student Profile Projects on School Democracy - Nindya Aulia Azzahra; Firman Umar; Najamuddin Najamuddin (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
Conventional student council elections often function as mere formalities, failing to serve as practical laboratories for democratic engagement and character development. This study evaluates the transformation of student elections through the Pancasila Student Profile Strengthening Project (P5) at Junior High School 1 Polongbangkeng Utara. The research focuses on three key dimensions: student participation levels, the implementation of democratic principles, and the development of civic skills among candidates. Employing a descriptive qualitative methodology, the study engaged teachers, students, and candidate pairs as primary informants. Data were gathered through interviews, systematic observation, and documentation, followed by analysis using data condensation, visualization, and conclusion drawing. Data validity was established via source triangulation. The findings demonstrate that: student participation reached an "excellent" threshold under the P5 framework; core democratic principles—direct, general, free, confidential, honest, and fair—were rigorously integrated into the electoral process; and candidate pairs exhibited "excellent" civic competencies. This research concludes that embedding student elections within the P5 framework significantly enhances democratic citizenship competencies. It offers a scalable pedagogical model for educational institutions to transform routine administrative procedures into meaningful, value-driven character-building experiences. Consequently, this approach bridges the gap between theoretical civic education and practical democratic participation in a secondary school context